Survival outcomes in canine nasal tumors treated with megavoltage radiation therapy with or without toceranib phosphate: a retrospective study of 279 cases - Rui Mizuno; Takashi Mori (American Journal of Veterinary Research, 2026)
Abstract Objective To evaluate whether adjunctive toceranib phosphate improves survival time in dogs with nasal tumors treated with megavoltage radiation therapy using a simplified 2-tier, CT-based staging system. Methods The medical records of 279 client-owned dogs with nasal tumors that underwent CT and megavoltage radiation therapy from 2015 through 2024 were retrospectively reviewed. Dogs were classified as stage I (no cribriform plate destruction) or stage II (cribriform plate destruction present). Survival time was analyzed using Kaplan-Meier methods and Cox proportional hazards models. Results The median survival time was longer in stage I than in stage II (468 vs 191 days). Toceranib phosphate was administered to 44 dogs. In the overall cohort, dogs treated with toceranib phosphate had longer survival times than untreated dogs (389 vs 250 days). Stage-specific analysis revealed no survival benefit in stage I. In contrast, toceranib phosphate was associated with prolonged survival in stage II. Multivariable analysis confirmed that toceranib phosphate was associated with improved survival in the overall cohort and in stage II but not in stage I. Conclusions Adjunctive toceranib phosphate was associated with improved survival in dogs with nasal tumors with cribriform plate destruction, whereas no benefit was observed in dogs without cribriform plate destruction. These findings indicate that the therapeutic effect of toceranib phosphate is stage dependent. Clinical Relevance A stage-based treatment approach may be appropriate in canine nasal tumors, with radiation therapy alone for stage I disease and combination therapy with toceranib phosphate for stage II disease.